2022
DOI: 10.4236/jhrss.2022.103037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Human Capital Development on Employee Retention in Nigerian Universities

Abstract: In higher institutions, the retention of employees is a serious concern due to high turnover rates. In this work, the relationship between human capital development (HCD) and employee retention (ER) in some selected tertiary institutions around Nigeria was examined. HCD was measured using training and development (TD) and career planning (CP) as proxy variables. On the other hand, ER was measured using employee motivation (M), workplace flexibility (WPF), and work-life balance (WLB). Two regression models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(70 reference statements)
2
1
0
Order By: Relevance
“…The results of hypothesis testing show that appropriate career development is able to strongly encourage an increase in organizational culture more optimally in employees of the Village Government Office in Jabung District, Malang Regency. This is in accordance with the results of previous research Zhu Jia-jun & Song Huaming ( 2022) and (Bilkisu et al, 2022) which concluded that career development has a positive and significant effect on organizational culture.…”
Section: The Effect Of Career Development On Organizational Culturesupporting
confidence: 93%
“…The results of hypothesis testing show that appropriate career development is able to strongly encourage an increase in organizational culture more optimally in employees of the Village Government Office in Jabung District, Malang Regency. This is in accordance with the results of previous research Zhu Jia-jun & Song Huaming ( 2022) and (Bilkisu et al, 2022) which concluded that career development has a positive and significant effect on organizational culture.…”
Section: The Effect Of Career Development On Organizational Culturesupporting
confidence: 93%
“…In reference to theme 1 in Table 6, This dedication to acknowledging and addressing the challenges faced by its employees, especially female ICT professionals, underscores the organization's commitment to creating a workplace that is supportive of a harmonious integration of professional and personal spheres. The findings are in tandem with Abubakar, Oluwade and Ibrahim (2022), Forge (2022) and Panda (2019) who found that, as employees navigate the demands of their professional lives, the boundaries between work and personal time have blurred, prompting a critical examination of the policies and practices that govern the modern workplace. Furthermore, Telkom's strategy for tackling work-life balance concerns, encompassing the well-being of its employees, aligns with findings from studies conducted by Carnevale and Hatak (2020), Maddox-Daines (2023), and Saxena and Gautam (2021).…”
Section: Demographic Variables and Work-life Balance Challengessupporting
confidence: 53%
“…Work-life balance, once considered a personal aspiration, has transformed into a strategic imperative for organizations seeking to attract, retain, and optimize their human capital. As employees navigate the demands of their professional lives, the boundaries between work and personal time have blurred, prompting a critical examination of the policies and practices that govern the modern workplace (Abubakar, Oluwade & Ibrahim, 2022, Forge, 2022, Panda, 2019. The HR function, traditionally tasked with personnel management, now plays a central role in crafting and implementing initiatives that nurture a harmonious coexistence of work and life.…”
Section: Introductionmentioning
confidence: 99%